Ferroptosis: Mechanism and potential applications in cervical cancer - Chang, Xiangyu; Miao, Jinwei (Frontiers in Molecular Biosciences, 2023)
Ferroptosis is a distinct form of cell death mechanism different from the traditional ones. Ferroptosis is characterized biochemically by lipid peroxidation, iron accumulation, and glutathione deficiency. It has already demonstrated significant promise in antitumor therapy. Cervical cancer (CC) progression is closely linked to iron regulation and oxidative stress. Existing research has investigated the role of ferroptosis in CC. Ferroptosis could open up a new avenue of research for treating CC. This review will describe the factors and pathways and the research basis of ferroptosis, which is closely related to CC. Furthermore, the review may provide potential future directions for CC research, and we believe that more studies concerning the therapeutic implications of ferroptosis in CC will come to notice.